Characteristics of Polymeric Fiber Reinforced Cementitious Composite (PFRCC) under Uniaxial Compression - Shwan Hussain Said; Khamees Nayyef Abdulhaleem; Ahmed Abdalhafedh Mustafa Al-Shaar (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
This study aimed to evaluate the compressive characteristics and toughness of polymeric fiber reinforced cementitious composites (PFRCC). In the experimental program, polyvinyl alcohol (PVA) fibers were used to prepare two groups of PFRCC cylinders with different fiber contents. The main factor considered in this study was the reinforcing index. Several parameters were investigated, i.e. compressive strength, elastic modulus, strain at peak stress, Poisson’s ratio and toughness of PFRCC. The results revealed that there was a reduction in both compressive strength and elastic modulus as the reinforcing index increased, while a significant increase in the strain at peak stress was observed. Moreover, a comparison was made between different methods of toughness estimation and it was found that 7.9 was the best reinforcing index for PVA fibers based on the energy absorption performance and ductility of PFRCC. Furthermore, an empirical model is proposed in this paper to predict the PFRCC-PVA compressive stress-strain curve. The proposed model features new formulas to calculate a number of important coefficients to plot the curve based on the reinforcing index value. Besides that, the model had good convergence compared to the experimental results, with perfect values for both variance and correlation coefficient.